PENINGKATAN KEMAMPUAN KOGNITIF ANAK USIA 4-5 TAHUN MELALUI PERMAINAN TRADISIONAL CONGKLAK DI TK AL-ZIQRI KOTA PADANG - Evi Desmariani; Zulfahman Siregar; Sri Ayu Nengsih; Didiek Wahyudi (Jurnal Riset Pendidikan Dasar Dan Karakter, 2021)
This research was motivated during the learning process at the preparation center, with the activity of sticking, the child was not able to paste the numbers according to the number of orange trees and when the teacher asked how many orange trees, the child was not able to add how many orange trees. This study aims to improve cognitive abilities of children aged 4-5 years through the traditional game of congklak in Al-Ziqri Kindergarten, Padang City. This type of research is classroom action research (PTK) which is carried out in two cycles. Each cycle consists of 3 meetings. While the data analysis technique uses the percentage formula and uses a frequency distribution table. Research procedures ranging from planning, implementation, observation and reflection. The results of the research from each cycle carried out showed that there was an increase in cognitive abilities in children in counting many objects from one to ten and recognizing the concept of numbers through congklak traditional game activities. Including the traditional games activity of congklak in counting many objects one to ten in the pre-action 20%, continuing to cycle I with a result of 26%, in cycle II with a result of 83%. While the ability to recognize the concept of numbers in pre-action 10% continues to cycle I with a result of 30% in cycle II with result of 80%. It can be concluded that the traditional game of congklak can increase the cognitive level of children aged 4-5 years in Al-Ziqri Kindergarten, Padang City.